Clinically important associations of pleurodesis success in malignant pleural effusion: Analysis of the TIME1 data set. Issue 7 (17th December 2019) - Mercer, Rachel M.; Macready, Jessica; Jeffries, Hannah; Speck, Nicole; Kanellakis, Nikolaos I.; Maskell, Nick A.; Pepperell, Justin; Saba, Tarek; West, Alex; Ali, Nabeel; Corcoran, John P.; Hallifax, Robert J.; et al.
ABSTRACT: Background and objective: Chemical pleurodesis is performed for patients with MPE with a published success rate of around 80%. It has been postulated that inflammation is key in achieving successful pleural symphysis, as evidenced by higher amounts of pain or detected inflammatory response. Patients with mesothelioma are postulated to have a lower rate of successful pleurodesis due to lack of normal pleural tissue enabling an inflammatory response. Methods: The TIME1 trial data set, in which pleurodesis success and pain were co‐primary outcome measures, was used to address a number of these assumptions. Pain score, systemic inflammatory parameters as a marker of pleural inflammation and cancer type were analysed in relation to pleurodesis success. Results: In total, 285 patients were included with an overall success rate of 81.4%. There was a significantly higher rise in CRP in the Pleurodesis Success group compared with the Pleurodesis Failure group (mean difference: 19.2, 95% CI of the difference: 6.2–32.0, P = 0.004) but no significant change in WCC. There was no significant difference in pain scores or analgesia requirements between the groups. Patients with mesothelioma had a lower rate of pleurodesis success than non‐mesothelioma patients (73.3% vs 84.9%, χ 2 = 5.1, P = 0.023). Conclusion: Change in CRP during pleurodesis is associated with successful pleurodesis but higher levels of pain are not associated. Patients with mesothelioma appear less likely to undergo successful pleurodesis than patients with other malignancies, but there is still a significant rise in systemic inflammatory markers. The mechanisms of these findings are unclear but warrant further investigation. Abstract : Inflammation, as evidenced by a greater rise in CRP levels, is associated with pleurodesis success but there is no association between success and degree of pain after pleurodesis. Patients with mesothelioma are more likely to experience pleurodesis failure but the mechanisms for this are unclear. See related Editorial